Contribution of Glass Material to the Circular Economy: Recycling and Reuse Approaches - Emine Merve Müderrisoğlu (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
In the construction industry, although glass is an indispensable building material due to its structural, aesthetic, and functional properties, the material’s disposal at the end of its life cycle -as well as the raw material extraction and production processes required for new materials- contributes to an increase in environmental issues. This study aims to examine the contributions of recycling and reusing glass materials to the circular economy. Within the scope of this research, the life cycle of glass-based materials has been analyzed, and sustainable projects implementing reuse and recycling applications have been investigated. The findings indicate that by reducing glass waste and enhancing resource, environmental problems can be mitigated, thereby increasing sustainability in the construction sector.